Evaluation of a Pakistani Food Photographs Atlas - Kulsoom, Tanzeela; Mushtaq, Shumaila; Hakeem, Rubina (Nurture, 2008)
Food photographs are often considered an important aid in assessment of dietary intakes. As part of a project for development of Pakistani Food Photograph Atlas (PFA), photographs of a large number of foods in various portion sizes had been taken few years back by one of the authors. The work was halted for some reasons and before resumption of the task it was considered necessary to evaluate the usefulness of available photographs for preparation of PFA. The purpose of this study was thus to identify the food items needed for Pakistani Food Atlas and the extent to which the available photographs fulfill that need. Determination of number and kind of food photographs required for the food photographic atlas, was done through a sample population survey of frequency of food intake. Available photographs were evaluation in terms of fulfillment of need and representation of real foods. A total of 78 foods were identified as required, photographs of 66 of those foods were available. In general food photographs represented the real foods (76-100% correct answers) but in a few cases due to the low quality of the pictures the subjects found it difficult to identify either the food or its correct quantity. Need for minimizing the list was essential, it’s suggested to take at least four portion photograph for each food ingredient, which is lacking.